Computerized music-based intervention module for auditory processing and working memory in older adults - Ramadas, Vaishnavi; Vaidyanath, Ramya; Uppunda, Ajith Kumar; Viswanathan, Sushma (Frontiers in Computer Science, 2023)
The contribution of technology to the field of health is vast, both in diagnosis and management. More so, the use of computer-based intervention has become increasingly widespread over the past decade. Human beings experience a decline in auditory processing and cognitive skills as they age, consistent with deterioration of other bodily functions. In addition, speech perception abilities in both quiet and in the presence of noise are impacted by auditory processing abilities and cognitive skills such as working memory. This pilot study explored the use of music as an intervention for improving these skills and employed a computerized delivery of the intervention module. A battery of tests was carried out to assess the baseline auditory processing and working memory skills in eight older adults between the ages of 56 and 79 years, all of whom had normal hearing. Following the assessment, a short-term computerized music-based intervention was administered. The style of music chosen was Carnatic classical music, a genre widely practiced in Southern India. The intervention module involved note and tempo discrimination and was carried out for a maximum of 10 half-hour sessions. The multi-level intervention module was constructed and administered using Apex, a software commonly used for psychoacoustic behavioral experiments. Following the intervention, the auditory processing and cognitive skills of the participants were reassessed to study any changes in their auditory processing and working memory skills. There were positive changes observed in all the auditory processing and some of the working memory abilities. This paper discusses in detail the systematic structuring of the computerized music-based intervention module and its effects on the auditory processing and cognitive skills in older adults.